Processing sawdust waste into innovative eco-substrate through upskilling Batulappa village women's group - Dewi, Sartika; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Nurannisa, Andi; Damayanti, Wiwi (Transformasi: Jurnal Pengabdian Masyarakat, 2024)
[Bahasa]: Limbah serbuk gergaji dari hasil pengolahan kayu di Desa Batulappa menimbulkan dampak negatif bagi lingkungan, terutama pencemaran udara akibat pengelolaan yang tidak optimal. Program pengabdian masyarakat ini bertujuan untuk mengatasi permasalahan limbah serbuk gergaji tersebut dengan memberdayakan Kelompok Perempuan Desa Batulappa melalui berupa Upskilling mitra dalam pengolahan limbah serbuk gergaji menjadi Eco-Substrate Innovative. Mitra dalam program ini adalah 15 anggota Kelompok Perempuan Desa Batulappa yang tergabung dalam divisi SDM dan Pengelolaan Lingkungan Hidup. Metode yang digunakan meliputi penyuluhan, pelatihan, dan pendampingan berbasis partisipasi masyarakat (society participatory). Hasil evaluasi menunjukkan peningkatan signifikan, yaitu rata-rata 90% dari aspek pengetahuan dan keterampilan dalam mengolah limbah serbuk gergaji, dimana anggota mitra berhasil memahami dan menguasai teknik pengolahan serbuk gergaji menjadi produk bernilai ekonomis berupa Eco-Substrate Innovative. Selain itu, mitra juga memperoleh keterampilan tambahan, seperti pengemasan, pelabelan, pemasaran, dan pengelolaan keuangan sederhana. Melalui program pengabdian ini, mitra mampu mentransformasi limbah serbuk gergaji menjadi produk inovatif yang ramah lingkungan, sekaligus berpotensi untuk dapat meningkatkan kesejahteraan ekonomi bagi Kelompok Perempuan Desa Batulappa. Kata Kunci: eco-substrate innovative, fermentasi, media tanam, serbuk gergaji, society participatory [English]: Sawdust waste from wood processing in Batulappa Village has a negative impact on the environment, especially air pollution due to suboptimal management. This community service program aims to overcome the problem of sawdust waste by empowering the Batulappa Village Women's Group by processing sawdust waste into Innovative Eco-Substrate. The partners in this program were 15 Batulappa Village Women's Group members of the Human Resources and Environmental Management division. The methods used include extension, training, and mentoring based on community participation (society-participatory). The evaluation results show a significant increase, namely an average of 90% in terms of knowledge and skills in processing sawdust waste, where partner members succeeded in understanding and mastering the technique of processing sawdust into economically valuable products in the form of Innovative Eco-Substrate. In addition, partners also gained additional skills, such as packaging, labeling, marketing, and simple financial management. Through this community service program, partners can transform sawdust waste into innovative, environmentally friendly products while also having the potential to improve economic welfare for the Batulappa Village Women's Group. Keywords: eco-substrate innovative, fermentation, planting media, sawdust, society participatory